Reinterpretasi Makna Hijrah dalam QS. al-Nisa Ayat 100: Sebuah Respon atas Fenomena Hijrah di Kalangan Artis - Izza Royyan (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2020)
This article aims to explain the discourse of hijrah that is rife in society. This phenomenon becomes interesting to discuss because the meaning of hijrah which historically is a historic sacred event of Muslims, is an event to leave Mecca and move to another place. However, if we look at the current context of hijrah that is rife with showing Islamic identity. By using the contextual theory that was initiated by abdullah saeed, this article tries to encounter the meaning behind hijrah that contained in the Qur'an. This article more specifically focuses on Qs. al-Nisa verse 100, by looking at the context at the time of the decline of the verse, sees the interpretation of the hijrah by classical commentators to modern and looks for meaning in the present context which is certainly different from the past. This research shows that there is a shift in meaning from the hijrah in the past where the values ​​of hijrah are shown physically in the form of changes in Muslim identity such as clothing, ways of speaking and so on. Hijra, based on contextual meaning, is changes all dimension in life. Such as, reconciliation, humanism, etc.